Measurement of Strong Shock Pressure - Hajime Takada; Daisuke Fujimaki; Takao Tsuboi (Shock and Vibration)
This paper deals with measurement of a strong shock pressure like an imploding detonation of over 1 GPa which cannot be measured directly with currently available commercial pressure transducers. After the transfer functions of three kinds of materials were measured using a shock tube, Teflon was selected as a shock absorber. As an example of pressure beyond the limit of the pressure transducer, we tried to measure pressure at the center of an imploding detonation. From this measurement, we could estimate the pressure peak of about 1.7 GPa.